Examining the psychometric properties of the PCL-5 in a black community sample using item response theory. (April 2022) - Mekawi, Yara; Silverstein, Madison W.; Walker, Aisha; Ishiekwene, Martha; Carter, Sierra; Michopoulos, Vasiliki; Stevens, Jennifer S.; Powers, Abigail
Abstract: Black Americans are more likely to be exposed to certain types of traumatic events and experience posttraumatic stress disorder (PTSD) compared to other racial groups. Consequently, sound assessment of PTSD in this underserved and understudied population is necessary to develop and accurately answer research questions about etiology and intervention efficacy. However, the item-level psychometric properties of one of the most commonly used assessment tools, the PTSD Checklist for DSM-5 (PCL-5), has yet to be examined among Black Americans. To address this gap, we used item response theory (IRT) to assess item difficulty and discrimination in a sample of Black American adults ( n = 307). We employed a graded response model with all 20 items of the PCL-5 loading on to a latent PTSD factor. At clinically significant levels of PTSD, the most discriminating items were flashbacks, inability to experience positive emotions, and nightmares and the least discriminating items were cued emotional distress, diminished interest, and hypervigilance. These results emphasize the importance of flashbacks, inability to experience positive emotions, and nightmares and deemphasize the importance of hypervigilance and sleep difficulties when assessing for clinically significant symptoms of PTSD in Black Americans. Treatment implications include a nuanced approach towards hypervigilance. Highlights: Research on accurate assessment of PTSD among Black Americans is scarce. Item-level psychometric properties of the PCL-5 have not been examined. We used item response theory to assess item difficulty and discrimination Most discriminating items were flashbacks and inability to experience positive emotions. Least discriminating items were cued emotional distress and diminished interest.